2014
DOI: 10.1016/j.ijid.2014.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and type distribution of human papillomavirus among women older than 18 years in Egypt: a multicenter, observational study

Abstract: The overall prevalence of HPV in Egypt was 10.4% and was highest (9.2%) amongst women aged 45-54 years. These data provide important reference information for public health authorities considering HPV prevention in Egypt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 15 publications
7
18
0
Order By: Relevance
“…In general, the women who participated in this study showed poor knowledge of the major symptoms and risk factors of cervical cancer. This result is similar to that reported by many other studies conducted in Arabic countries (El Mhamdi, Bouanene, Mhirsi, Bouden & Soltani, ; El‐Hammasi et al., ; Maaita & Barakat, ; Shaltout et al., ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In general, the women who participated in this study showed poor knowledge of the major symptoms and risk factors of cervical cancer. This result is similar to that reported by many other studies conducted in Arabic countries (El Mhamdi, Bouanene, Mhirsi, Bouden & Soltani, ; El‐Hammasi et al., ; Maaita & Barakat, ; Shaltout et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…These results suggest that although many of the women know that a link exists between cervical cancer and sex, the mechanism of HPV infection is not understood by most of them (Low et al., ; Waller, McCaffery & Wardle, ,b). A study performed in Egypt found that 32.5% think that cervical cancer is caused by a viral infection, which is near to the 35% recorded in one of our earlier studies (Shaltout et al., ).…”
Section: Discussionmentioning
confidence: 42%
“…But, according to these studies in women with normal cervical cytology conducted in Turkey, the cumulative rates of HPV types other than type 16 or type 18 are more common as also shown in our study. Similarly, total hrHPV types other than type 16 and type 18 were more common in the studies from Egypt and Kingdom of Bahrain [16,17]. In a meta-analysis, the HPV types 16 and 18 are most commonly described in pre-neoplastic and cancer cases, although the relative contribution of HPV type 16 and HPV type 18 is substantially lower in cytologically normal women [1].…”
Section: Discussionmentioning
confidence: 88%
“…Persistent infections with carcinogenic Human papillomavirus (HPV) types are well-recognized causes of cervical cancers. More than 100 different HPV types have been identified, and genotypes 16,18,31,33,34,35,39,45, 51, 52, 56, 58, 59, 66, 68 and 70 are associated with the development of cervical intraepithelial neoplasia grade 2, or 3 and invasive cervical cancer and these genotypes have been classified as high-risk group [2]. Thus, HPV genotype detection is helpful procedure in reducing cervical cancer incidence [3].…”
Section: Introductionmentioning
confidence: 99%
“…For the HPV testing, specimens were analyzed by the HPV Direct Flow Chip system, which is intended for simultaneous detection and genotyping of 36 HPV types (high-risk HPV [16,18,26 , by direct PCR, followed by reverse dot blot automatic hybridization, based on DNA-flow technology and colorimetric detection with the automatic e-BRID R System [13]. The amplification was carried out by PCR from crude-cell extracts, by using the PCR Mix and Phire Hot Start II DNA Polymerase (MAD-003930MU-P-E-30, Master Diagnostica, Granada, Spain).…”
Section: Data Collectionmentioning
confidence: 99%